Implementasi Kebijakan Moneter Ekonomi Indonesia Periode 2003-2009: - Sukarna Eksyar; Iwan Apribadi; Evi Novita (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2020)
The method used by the authors in this study is a qualitative method with the results of the presentation in a descriptive form, namely by collecting actual data by carrying out a literature study of some written literature. This research uses the type of library research (library research). Literature research is research that uses written data such as books, books, magazines, journals and others. To get the best data, certain techniques are taken, including the most important one is research, which is collecting material by reading books, journals and other forms of material or commonly referred to as library research. one type of research through libraries. The results of the research show that M. Umer Chapra's thoughts about monetary policy instruments. In the economy can be an important discourse to be considered and studied even further implemented in Indonesia. It is not impossible to apply M. Umer Chapra's thinking in Indonesia. Growth in terms of assets has also proven that Islamic banks are a bank model that is ideal for driving the progress of the country's economy. But in terms of service quality, Islamic banks must catch up with conventional banks that have already been established.